A multiplex method for detection of glucose‐6‐phosphate dehydrogenase (G6PD) gene mutations. (20th July 2015) - Zhang, L.; Yang, Y.; Liu, R.; Li, Q.; Yang, F.; Ma, L.; Liu, H.; Chen, X.; Yang, Z.; Cui, L.; He, Y.
Summary: Introduction: Glucose‐6‐phosphate dehydrogenase (G6PD) deficiency is the most common human enzyme defect caused by G6PD gene mutations. This study aimed to develop a cost‐effective, multiplex, genotyping method for detecting common mutations in the G6PD gene. Methods: We used a SNaPshot approach to genotype multiple G6PD mutations that are common to human populations in South‐East Asia. This assay is based on multiplex PCR coupled with primer extension reactions. Different G6PD gene mutations were determined by peak retention time and colors of the primer extension products. Results: We designed PCR primers for multiplex amplification of the G6PD gene fragments and for primer extension reactions to genotype 11 G6PD mutations. DNA samples from a total of 120 unrelated G6PD‐deficient individuals from the China–Myanmar border area were used to establish and validate this method. Direct sequencing of the PCR products demonstrated 100% concordance between the SNaPshot and the sequencing results. Conclusion: The SNaPshot method offers a specific and sensitive alternative for simultaneously interrogating multiple G6PD mutations.